Economic Issues with Specialty Crops - Coltrain, David; Neufeld, Liz; Boland, Michael; Marr, Chuck (My University, 1998)
This publication provides an overview of the Kansas specialty crop industry.
MF2427_1999_08
Keywords: MF2427; Economics; Crops; MF